Risk Analysis in Manual Financial Processes at PT XYZ Using the Fmea (Failure Mode Effect Analysis) Method - Annisa Putri Pratama; Endang Chumaidiyah (Eduvest - Journal of Universal Studies, 2025)
Manual financial processes in an organization often pose various operational risks, such as delays in recording, duplication of data, and input errors, especially in administrative systems that have not been digitized. This study aims to analyze potential failures and prioritize risks in the financial recording and collection process at PT XYZ using the Failure Mode and Effect Analysis (FMEA) method. The research is carried out by identifying the main activities, formulating potential failures, and providing an assessment of the severity, occurrence, and detection capabilities of each potential failure. The Risk Priority Number (RPN) value is calculated to determine the risk priority. The results showed that out of the eight main activities, 32 potential failures were found with RPN values varying between 72 to 315. Some activities, such as data transfer between sheets, manual financial record-keeping, and monthly arrears checks, have the highest risk. These findings confirm the need for digitization and system improvement as a risk mitigation strategy in manual financial processes.